Body composition: How should it be measured? Does it affect sport performance? - Houtkooper, L. B.; Going, S. B. (1994)
1. Physique is defined by three interrelated aspects of the body: size, structure, and composition. 2. Body composition refers to the amounts of constituents in the body at atomic, molecular, cellular, tissue-system, and whole-body levels. 3. The simplest and most common model of body composition partitions the body into two major components (compartments)--fat mass and fat-free mass. 4. Accuracy of field methods for estimation of the body composition of sport participants depends upon selection of appropriate models and measurement methods, skill of individuals taking the measurements, and use of prediction equations specific to the appropriate gender and age. 5. Appropriate methods and careful measurements make it possible to estimate relative body fat mass (% body fat) with an error of approximately 3-4% fat and fat-free mass with an error of 2.0-2.5 kg. 6. The ranges of % body fat for elite competitors vary by sport and by gender within a sport. 7. Excess body fat negatively influences physical performance by adversely affecting mechanical, metabolic, and thermoregulatory attributes of the activity. 8. High ratios of fat-free mass to fat mass at a given body weight are generally positively related to sport performance, but too little body fat results in deterioration in both health and performance. 9. The ideal relative fat mass or fat-free mass for a competitor in a specific sport is difficult to define because body size, body structure, and many other factors also contribute to competitive success.